ISSUES OF EFFECTIVE PROTECTION OF PUBLIC HEALTH AND THE NATION’S GENE POOL FROM DRUG-RELATED CRIMES - Abduqodirov Sherzod Yoqubjonovich (Modern American Journals, 2026)
This article analyzes Decree No. PD-207 of 3 November 2025 of the President of the Republic of Uzbekistan, aimed at strengthening comprehensive protection of public health and the nation’s gene pool from drug addiction and drug-related crimes. The study clarifies the conceptual scope of “public health” and “nation’s gene pool” as policy-legal categories and systematizes the Decree’s approach as an integrated set of regulatory-legal, operational-preventive, organizational, and educational measures. Particular attention is given to the prioritization of youth protection, the proposed tightening of criminal sanctions for organized drug crime, Internet-based distribution, and illegal laboratories, as well as the introduction of electronic control over precursor circulation. The paper highlights the Decree’s reform agenda, including the preparation of a new edition of the law on narcotic drugs and psychotropic substances, the formation of a distinct chapter in the Criminal Code on crimes against public health and the nation’s gene pool, the strengthening of liability for offenses involving minors, restrictions on early conditional release, and the development of AI-enabled mechanisms to detect and block online drug markets. The article concludes that the Decree institutionalizes a more systematic, stringent, and digitally supported model of counter-narcotics governance, combining deterrence with targeted prevention and technological oversight.
Keywords: Drug addiction; drug-related crimes; public health protection; nation’s gene pool; youth safeguarding; criminal liability; organized drug crime; Internet drug trafficking; precursors control; electronic monitoring; legal reform; artificial intelligence.